Longer Life, Higher Welfare? - Michael Grimm; Kenneth Harttgen (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Whereas life expectancy continues to increase in most industrialized countries many developing and transition countries are today confronted with decreases in life expectancy. Usual measures employed to compare welfare over time and space fail to deal with such demographic change and may lead to the so-called ?repugnant? conclusion that lower life expectancy involves higher welfare per capita. We illustrate this type of transmission channel using various welfare criteria and reference populations. We also consider feed-back effects from the demography on the economy using a neo-classical growth model. We show that the ?repugnant? conclusion can be avoided if we choose a lifetime welfare measure instead of a period (or snapshot) welfare measure. All concepts are illustrated empirically using a small sample of developed and developing countries.
Keywords: I31; D63; J11; 330; Life expectancy; repugnant conclusion; welfare comparisons